Dynamic Cord Compression Causing Cervical Myelopathy - Andrei Fernandes Joaquim; Griffin R. Baum; Lee A. Tan; K. Daniel Riew (Neurospine, 2019)
Due to the highly mobile nature of the cervical spine, and the fact that most magnetic resonance imagings (MRIs) and computed tomography scans are obtained only in one single position, dynamic cord compression can be an elusive diagnosis that is often missed and not well-understood. In this context, dynamic MRI (dMRI) has been utilized to improve the diagnostic accuracy of cervical stenosis. We performed a literature review on dynamic cord compression in the context of cervical spondylotic myelopathy (CSM), with particular emphasis on the role of dMRI. Cadaveric studies report that the spinal cord lengthens in flexion and the spinal canal dimension increases, whereas the spinal cord relaxes and shortens in extension and the spinal canal decreases. These changes may lead to biomechanical stress in the spinal cord with movement, especially in patients with critical cervical stenosis. The majority of the studies using dMRI in CSM reported that this imaging modality is more sensitive at detecting cervical cord compression compared to routine MRIs done in a neutral position, especially with the neck in extension. Dynamic MRI was also useful to diagnose dynamic cervical cord compression after laminectomies in patients with clinical deterioration without evident cord compression on neutral static MRI. Finally, dMRI is more sensitive in detecting stenosis in patients with CSM than in those with ossification of the posterior longitudinal ligament (OPLL), likely because OPLL patients often have a more limited range of motion than CSM patients. Thus, dMRI is a promising new tool that can help spine surgeons in diagnosing and treating CSM.